Framework for creating a qualified medical device development tool of autoinjectors - Machal, Marlon Luca (Frontiers in Medical Technology, 2023)
Objectives Autoinjectors are pivotal for precise self-administration of medications across a wide range of medical conditions. Nevertheless, the absence of a dedicated Medical Device Development Tool (MDDT) for autoinjectors represents a gap that may result in variations in the quality and regulatory compliance of autoinjectors as components of combination products. This research aim is to utilize the recently introduced Primary Functions outlined in ISO 11608-1:2022 with the title “Needle-based injection systems for medical use. Requirements and test methods. Part 1: Needle-based injection systems” to create a comprehensive MDDT framework tailored specifically for autoinjectors. Methods To support the creation of the framework, the analysis of the FDA MDDTs that were already approved, FDA's design controls regulations, FDA's guidance related to autoinjectors, and the Primary functions outlined in ISO 11608-1:2022 were utilized. Results The research identifies the Primary Functions in autoinjector to be Holding Force, Cap Removal Force, Activation Force, Extended Needle Length, Injection Time, Dose Accuracy and Needle Guard Lockout. Leveraging these Primary Functions and the FDA's MDDT approach, the research aims to bridge the gap by proposing a structured framework for the development of a specific MDDT tailored to autoinjectors. Conclusion This study presents a MDDT framework tailored to the development of autoinjectors for drug delivery. This framework provides a structured methodology to support predictability and effectiveness of the autoinjector development and support regulatory review process, thereby expediting FDA approval for autoinjectors as part of combination product.